Penerapan Model Contextual Teaching and Learning (CTL) berbantuan media audiovisual untuk meningkatkan hasil belajar IPAS Kelas III SD 1 Jati Wetan - Arif Budianto; Erik Aditia Ismaya; Redjeki Handayani; Linda Ratna Sari (STKIP Subang, 2025)
The study aims to determine the improvement of the learning outcomes of the students using the Contextual Teaching and Learning (CTL) model supported by the learning media audiovisual in IPAS subjects. The type of research used in this research is classroom action research. Data collection using interviews, observations, written tests, and documentation. Class Action Research was conducted in SD 1 Jati Wetan class III with 9 students. The results obtained in this study are showed improvement in each cycle. In the pre cycle the average value obtained is 66,66, in the first cycle is 69,44, and in the second cycle is 78,88. And the percentage of completeness in the pre cycle reaches 33,33%, in the first cycle is 55,55%, and in the second cycle is 88,88%. Thus, it can be concluded that the application of Contextual Teaching and Learning (CTL) in IPAS subjects in elementary school can improve learning outcomes.